Strandfontein coastal development: proposals for a regional recreation amenity - Daniels, David P (School of Architecture, Planning and Geomatics, 2025)
The basic aim of the planner - stated in very simple terms is to create a better social and physical environment for mankind. With such a broad objective the planner has to be concerned with almost every human experience. In the past certain aspects of planning, notably housing, have been strongly emphasised while other fields have been neglected. A field of planning which has often not been given sufficient attention both locally and overseas is recreation planning. This is a serious commission because if the planner is concerned with man's whole living environment, what people do in their leizure, time should be of' considerable interest to him. Marion Clawson, one of' the pioneers of' recreation research, writes about this problem as follows: With a few notable exceptions, the various physical, economic, social, political and other problems relating to outdoor recreation, have not been the subject of' serious research and study. In no small part, this has been due to· the fact that recreation has been equated to a degree with play, and both have been considered 1 beneath the dignity of serious research effort. In the first place, therefore, the purpose of this document is to make a contribution to the field of recreation research and to stimulate further investigation. This writer believes that recreation should be seen as a positive and pleasurable activity which performs a key function in the living patterns of' people. Any “quality of' life" evaluation must include the opportunities available for recreation and the nature and rate of' participation in recreation activities.